The Waiotapu earthquake of 1983, December 14 - Smith, Euan G. C.; Scott, Brad J.; Latter, John H. (Bulletin of the New Zealand Society for Earthquake Engineering, 1984)
The continual earthquake swarm activity in the Waiotapu-Waikite Valley area that commenced in April 1982, reached a climax on 14 December 1983 with the occurrence of a magnitude 5.1 shock at shallow depth, on or close to the Ngapouri fault, near Waiotapu. It was the largest event in this area for more than 40 years. Felt intensities reached MM VII and possibly MM VIII in the epicentral region and resulted in claims for $29,000 worth of damage. Although inadequate for the determination of a focal mechanism, first P-wave motions indicate that the earthquake produced east-west extension. On the assumption that the shock occurred on the Ngapouri fault (strike N55°E, northwest side down), this implies sinistral movement with a lesser dip slip component. Geodetic data are consistent with extention at N110°E in the region, although the magnitude of the strain is technically too small to be statistically significant.